2022
DOI: 10.3390/cells11121902
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Characteristics of Astrocytes and Microglia: A Possible Involvement in Aging and Diseases

Abstract: Although different regions of the brain are dedicated to specific functions, the intra- and inter-regional heterogeneity of astrocytes and microglia in these regions has not yet been fully understood. Recently, an advancement in various technologies, such as single-cell RNA sequencing, has allowed for the discovery of astrocytes and microglia with distinct molecular fingerprints and varying functions in the brain. In addition, the regional heterogeneity of astrocytes and microglia exhibits different functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 234 publications
1
8
0
Order By: Relevance
“…Comparisons between young and aged sham mice indicated genetic heterogeneity between cortex and hippocampus during aging. This is in agreement with a recent report that summarized the cellular and molecular heterogeneity of astrocytes and microglia in different brain regions in relation to aging and neurodegenerative diseases [24]. Through heatmap clustering of the average zscores for each group, our findings demonstrate that (1) the "Activated Microglia" and "Autophagy" are the top two upregulated pathways in the hippocampus, but not in the somatosensory cortex with aging, and (2) these pathways become pronounced following SCI in the cortex from aged but not young adult animals.…”
Section: Discussion (1260 Words)supporting
confidence: 94%
“…Comparisons between young and aged sham mice indicated genetic heterogeneity between cortex and hippocampus during aging. This is in agreement with a recent report that summarized the cellular and molecular heterogeneity of astrocytes and microglia in different brain regions in relation to aging and neurodegenerative diseases [24]. Through heatmap clustering of the average zscores for each group, our findings demonstrate that (1) the "Activated Microglia" and "Autophagy" are the top two upregulated pathways in the hippocampus, but not in the somatosensory cortex with aging, and (2) these pathways become pronounced following SCI in the cortex from aged but not young adult animals.…”
Section: Discussion (1260 Words)supporting
confidence: 94%
“…One possible source of these differences could be astrocyte densities which are known to differ in functions across brains regions. 57,58 Indeed, studies that have observed decrease in astrocytes in AUD are largely focused in brain regions where there are lower densities of astrocytes, 55,56,59 while the structures examined in the current study may have high densities of astrocytes; however, further investigation into astrocyte populations in the examined structures is needed. Importantly, it has been demonstrated that GFAP density does not change in rats chronically exposed to alcohol in the cerebellum.…”
Section: Discussionmentioning
confidence: 89%
“…However, the brain regions examined in these studies differed to the current study and were instead focused on the dorsolateral prefrontal cortex, orbitofrontal cortex and hippocampus, 54–56 and thus, like microglia (described above), astrocytes could demonstrate region‐specific responses to alcohol. One possible source of these differences could be astrocyte densities which are known to differ in functions across brains regions 57,58 . Indeed, studies that have observed decrease in astrocytes in AUD are largely focused in brain regions where there are lower densities of astrocytes, 55,56,59 while the structures examined in the current study may have high densities of astrocytes; however, further investigation into astrocyte populations in the examined structures is needed.…”
Section: Discussionmentioning
confidence: 92%
“…Age-related changes are observed not only in neurons but also in glial cells. 11 13 RNA sequencing of purified astrocytes from various regions of the brain has demonstrated up-regulation of inflammatory markers, components of the complement cascade, factors involved in synapse elimination, and others that are similar to those observed in reactive astrocytes. 14 16 In the optic nerve head, astrocytes form the direct cellular environment of the unmyelinated RGC axons.…”
Section: Introductionmentioning
confidence: 93%